Pengaruh Work Life Balance, Reward, dan Punishment terhadap Kinerja Karyawan pada CV. Hemon Kados Jaya di Kabupaten Semarang - Vinata Utari; Alean Kiatiani Hegy Suryana; Unna Ria Safitri (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Employee performance is one of the key factors determining organizational success. This study aims to examine the effect of work life balance, reward, and punishment on employee performance at CV. Hermon Kados Jaya in Semarang Regency. This research employed an associative quantitative approach. The population consisted of 100 employees, and 80 respondents were selected using the proportionate stratified random sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS software. The findings indicate that work-life balance has a positive and significant effect on employee performance (Sig. = 0.044 < 0.05). Reward has no significant effect on employee performance (Sig. = 0.359 > 0.05). Meanwhile, punishment has a positive and significant effect on employee performance (Sig. = 0.017 < 0.05). Simultaneously, work-life balance, reward, and punishment significantly affect employee performance (Sig. = 0.000 < 0.05), with a coefficient of determination (R²) of 0.795, indicating that 79.5% of employee performance is explained by these three variables, while the remaining 20.5% is influenced by other factors outside the research model. The study concludes that maintaining work-life balance and implementing fair and consistent punishment contribute to improving employee performance, whereas the existing reward system has not been effective in enhancing employee performance.